Anti-Biofilm Activity of Carnosic Acid from Salvia rosmarinus against Methicillin-Resistant Staphylococcus aureus - Valeria Iobbi; Valentina Parisi; Giulia Bernabè; Nunziatina De Tommasi; Angela Bisio; Paola Brun (Plants, 2023)
The Salvia rosmarinus “Eretto Liguria” ecotype was studied as a source of valuable bioactive compounds. LC-MS analysis of the methanolic extract underlined the presence of diterpenoids, triterpenoids, polyphenolic acids, and flavonoids. The anti-virulence activity of carnosic acid along with the other most abundant compounds against methicillin-resistant Staphylococcus aureus (MRSA) was evaluated. Only carnosic acid induced a significant reduction in the expression of agrA and rnaIII genes, which encode the key components of quorum sensing (QS), an intracellular signaling mechanism controlling the virulence of MRSA. At a concentration of 0.05 mg/mL, carnosic acid inhibited biofilm formation by MRSA and the expression of genes involved in toxin production and made MRSA more susceptible to intracellular killing, with no toxic effects on eukaryotic cells. Carnosic acid did not affect biofilm formation by Pseudomonas aeruginosa, a human pathogen that often coexists with MRSA in complex infections. The selected ecotype showed a carnosic acid content of 94.3 ± 4.3 mg/g. In silico analysis highlighted that carnosic acid potentially interacts with the S. aureus AgrA response regulator. Our findings suggest that carnosic acid could be an anti-virulence agent against MRSA infections endowed with a species-specific activity useful in multi-microbial infections.